1972-2022: the conception, reception and scope of Philippe Gauthier’s Symbola (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
This austere work is a landmark, but also bears the mark of the context of its writing (a “main” thesis of “Doctorat d’Etat”), of its author and of its intellectual filiation. It is the work of a historian, trained alongside André Aymard and Louis Robert, on an idea of Moses Finley, and finally a thesis directed by Édouard Will. A technical work, which opened many dossiers, it was also part of the history of law. It was well received by epigraphists (it earned its author the chair of epigraphy at the EPHE) and by a number of historians; it was also part of a vast renewal of studies devoted to the relations of cities with foreigners, which characterized the 1970’s to 1990’s (work on isopoliteia, metoikoi, proxenia, asylia, etc.), which has not dried up since. But the author’s institutional and even legal perspectives have given rise to significantly different approaches among historians. Moreover, some of the author’s historical conceptions (such as those set out in his conclusion) are now outdated, by many works, including later studies by Philippe Gauthier himself.
Keywords: Classical and hellenistic poleis; Greek law; justice; politeia; foreigners; treaties; isopoliteia; metoikia; symbolai; symbola; asylia; scholarship; historiography